ANALISIS RASIO LIKUIDITAS PENDEKATAN EMPIRIS DALAM EVALUASI KESEHATAN FINANSIAL PERUSAHAAN - Khoiru Sabila; Siti Murasih; Joni Hendra (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This study examines the importance of liquidity ratio analysis in evaluating a company's financial health, especially within the context of retail businesses that are particularly sensitive to economic fluctuations. Companies must effectively manage their finances to avoid declines in performance or bankruptcy. Financial performance is assessed through various financial ratios, including liquidity ratios, which measure a company's ability to meet short-term obligations. The research utilizes a descriptive quantitative method to explore the relationship between liquidity and financial health, emphasizing the necessity of adequate liquidity management for sustained operational success. The findings highlight the significant impact of liquidity on managerial decisions, investment strategies, and overall financial stability, advocating for the implementation of comprehensive financial analysis to ensure corporate well-being. Keywords: Analysis, Liquidity Ratio, Empirical Approach